Stock market liquidity: A case study of Karachi Stock Exchange - Hakim Ali Kanasro; Amanat Ali Jalbani; Mumtaz Ali Junejo (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2009)
A market is to be considered as liquid when large transactions are executed with a small impact on price. This paper identifies the position of stock market liquidity at Karachi Stock Exchange (KSE) during the period from 1985 to 2006. The analysis is based on using annual data of the listed firms at KSE and the data available on economic survey of the Government of Pakistan and other sources. For measurements of liquidity at KSE we have used three measuring tools as; Liquidity Analysis, Turnover Ratio and Size of Market to determine the liquidity issues at KSE. We provide the evidences of less stock market liquidity or to say illiquidity at Karachi Stock Exchange during the sample period. Consequently, market is still for behind in its efficiency, especially in liquidity hence it fails to attract new investors. We find that less liquidity causes less synchronicity in prices attracting less inventors and results is low size of market.
Keywords: 330; Stock Market Liquidity; Turnover ratio; Aggregate Market Capitalization; Size of Stock Market; Portfolio investors